Singularities of construction of static war-hour meters alternating-current - Петрище, М.О. (Proceedings of National Aviation University (archive), 2004)
The analysis of construction of static war-hour meters is carried out which are founded on use of specialized tools, which are intended for measurement of a active energy. The shortages of such methods concerning a possibility of unauthorized takeoff of an electric energy are marked through improper phasing of a current. The method is offered which allows to construct static war-hour meters insensitive to improper phasing of a current.